A sub-Neptune transiting the young field star HD 18599 at 40 pc. Issue 1 (27th March 2023) - de Leon, J P; Livingston, J H; Jenkins, J S; Vines, J I; Wittenmyer, R A; Clark, J T; Winn, J I M; Addison, B; Ballard, S; Bayliss, D; Beichman, C; Benneke, B; et al.
ABSTRACT: Transiting exoplanets orbiting young nearby stars are ideal laboratories for testing theories of planet formation and evolution. However, to date only a handful of stars with age <1 Gyr have been found to host transiting exoplanets. Here we present the discovery and validation of a sub-Neptune around HD 18599 , a young (300 Myr), nearby ( d = 40 pc) K star. We validate the transiting planet candidate as a bona fide planet using data from the TESS , Spitzer , and Gaia missions, ground-based photometry from IRSF , LCO , PEST , and NGTS , speckle imaging from Gemini, and spectroscopy from CHIRON , NRES , FEROS , and Minerva -Australis . The planet has an orbital period of 4.13 d , and a radius of 2.7 R ⊕ . The RV data yields a 3-σ mass upper limit of 30.5 M ⊕ which is explained by either a massive companion or the large observed jitter typical for a young star. The brightness of the host star ( V ∼9 mag) makes it conducive to detailed characterization via Doppler mass measurement which will provide a rare view into the interior structure of young planets.